Post-Dural Puncture Backache (PDPB) in Parturients Undergoing Caesarean Delivery Under Spinal Anaesthesia: A Cross Sectional Study (Medical Forum Monthly, 2021)
Objective: To determine the incidence of lower backache associated with spinal anesthesia given after cesarean delivery.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Department of anesthesia, Gujranwala Medical College, Gjuranwala from December 2020 to June 2021.Materials and Methods: In this cross sectional study, 300 patients / subjects were included from 20 to 40 of age, who were given spinal anesthesia before the cesarean section. While all the patients who were given any other type of second anesthesia as well after the spinal anesthesia during the course of the study, were excluded. All the patients were interviewed after 24 hours of spinal anesthesia and then after one week when coming for follow-up in the obstetrics out-patient department to examine and diagnose any backache related to spinal anesthesia. Primary outcome was the calculation of incidence of PDPB – backache after spinal anesthesia in patients of caesarian delivery. Outcome was stratified for age, BMI, first pass success and change of needle direction and post stratification chi square test was applied.Results: Among these 300 female, frequency of PDPB was recorded in 14.3% (n=43) of the cases whereas 85.7% (n=257) had no backache related spinal anesthesia. Among patients diagnosed having PDPB (backache), data analysis showed that in 29 (67%) cases more than one attempts were made to insert the needle in the spine. (p value 0.00001).Conclusion: Post-dural puncture backache (PDPB) can be among the common adverse effects of spinal anesthesia used for any type of surgery. Old age, obesity, multiple attempts to pass the spinal needle, bloody CSF and change of space after failure of 1st attempt were some factors significantly associated with backache related to spinal anesthesia.